EFFECT OF OVERLAP LENGTH AND ADHESIVE THICKNESS ON THE SHEAR STRENGTH OF JUTE FIBRE COMPOSITE AND FIBREGLASS COMPOSITE JOINTS - Sugiman; Aji Noven Setyawan; Agus Dwi Catur; Hilton Ahmad (Jurusan Teknik Mesin dan Industri, Fakultas Teknik, Universitas Mataram, 2026)
Adhesively bonded joints have attracted the attention of engineers for connecting different materials to develop lightweight structures. The materials that can be bonded include composite materials with different reinforcements, such as glass and natural fibres, but to achieve optimal strength, factors such as adhesive thickness and overlap length remain decisive. This study aims to determine the effect of overlap length and adhesive thickness on the shear strength of jute fibre-reinforced composite and glass fibre-reinforced composite joints. This study used single lap joints according to ASTM D1002. The overlap lengths varied by 15, 20, 25, and 30 mm, while the adhesive thicknesses varied by 0.2, 0.4, and 0.6 mm. This study found that joint strength decreases with increasing overlap length, whereas the effect of adhesive thickness depends on overlap length. At overlap lengths of 15 and 20 mm, joint strength increases with increasing adhesive thickness, whereas at 25 and 30 mm overlap lengths, it appears to remain constant. The optimal adhesive thickness is 0.4 mm. At an overlap length of 20 mm, the shear strength at adhesive thicknesses of 0.4 mm and 0.2 mm is 4.58 MPa and 3.71 MPa, respectively, or an increase of about 36% relative to the 0.2 mm thickness. The results imply that for hybrid jute and fibreglass composite joints, a short overlap length (i.e., 15 mm) and an adhesive thickness below 0.4 mm are recommended.